QARAQALPAQ NAQÍL-MAQALLARÍNDA BIYPATPA (BIYBIPATMA, BIYBI-FATIMA) OBRAZÍ HÁM ONÍŃ GENDERLIK-LINGVOKULTUROLOGIYALÍQ ANALIZI - Qosnazarova, Ulbolsın Quanıshbay qızı (SCIENCE and SOCIETY, 2026)
The earliest manifestations of the image of women in Karakalpak folklore date back to the distant past. That is, it is also connected with ancient religious concepts. In this article, we analyzed the formation of the Biypatpa (Fatima az-Zahra) cult among the female spiritual guides of the Karakalpak people and its linguocultural manifestations.